Metal Sub‐nanoclusters Confined within Hierarchical Porous Carbons with High Oxidation Activity. (11th March 2021) - Zhao, Xin; Kong, Xiangpeng; Wang, Fengliang; Fang, Ruiqi; Li, Yingwei
Abstract: Metal sub‐nanoclusters (SNCs) have shown great promise for a variety of catalytic reactions. However, the fabrication of stable metal SNCs simultaneously with high dispersion and high metal contents remains a challenge. Herein, we report a novel and versatile strategy for the synthesis of various bimetal SNCs stabilized within hierarchical porous carbons (HPC). This facile synthesis only involves the self‐assembly of a metal‐organic framework (MOF) as the precursor, a molten salt assisted pyrolysis process and the final metal replacement. The metal SNCs (mostly less than 0.8 nm) derived from the metal nodes of the MOF are exclusively confined and homogeneously dispersed throughout the organic ligands derived HPC at high loadings (up to 11.2 wt %). The obtained Cu‐Pd@HPC composite exhibits superior catalytic activity and recycling durability in the selective transformation of furfural to maleic acid, achieving 97.8 % yield of maleic acid with a TOF value as high as 20.1 h −1 under mild conditions. DFT calculations reveal that the introduction of Pd shifts the partial density of states of Cu toward the Fermi level, leading to stronger chemisorption of furfural to enhance the catalytic activity. Abstract : A novel and versatile strategy has been developed for the synthesis of bimetal sub‐nanoclusters (SNCs) stabilized within hierarchical porous carbons (HPC). The sizes of the homogeneous‐dispersion Cu‐M SNCs (M=Pd, Pt, or Ru) are mostly less than 0.8 nm even at high loadings up to 11.2 wt %. The as‐prepared Cu‐M@HPC catalysts exhibit excellent catalytic performances in the selective oxidation of furfural to maleic acid under mild reaction conditions.